Profiles of dual commitment to the occupation and organization: Relations to well-being and turnover intentions - Morin, A.; Meyer, John; McInerney, D.; Marsh, H.; Ganotice, F. (Springer New York LLC, 2015)
Work-relevant commitments have important implications for employee behavior and well-being, but the connections are complicated by the fact that commitments can be characterized by different mindsets and be directed at different targets. Recent developments in person-centered analytic strategies (e.g., latent profile analysis) have helped to address these complexities, particularly as they pertain to the interactions among the mindset of affective, normative, and continuance commitment to the organization. In the present study we extend application of the person-centered approach to identify profiles of commitment to two interrelated targets—the organization and the occupation—in a sample of 1,096 Hong Kong teachers. We identified seven distinct profiles reflecting both similarities and differences in the nature of the dual commitments across targets, and demonstrated differing patterns of turnover intentions and well-being across the profiles. Implications for commitment theory, future research, and practice are discussed.